Decreased Apoptotic Rate of Alveolar Macrophages of Patients with Idiopathic Pulmonary Fibrosis. (25th June 2012) - Drakopanagiotakis, Fotios; Xifteri, Areti; Tsiambas, Evaggelos; Karameris, Andreas; Tsakanika, Konstantina; Karagiannidis, Napoleon; Mermigkis, Demetrios; Polychronopoulos, Vlasis; Bouros, Demosthenes
Abstract : Introduction . Increased apoptosis of epithelial cells and decreased apoptosis of myofibroblasts are involved in the pathogenesis of IPF. The apoptotic profile of alveolar macrophages (AMs) in IPF is unclear. Aim . To investigate whether AMs of patients with IPF exhibit a different apoptotic profile compared to normal subjects. Methods . We analyzed, by immunohistochemistry, the expression of the apoptotic markers fas, fas ligand, bcl-2, and bax in AM obtained from bronchoalveolar lavage fluid (BALF) of 20 newly diagnosed, treatment-naive IPF patients and of 16 controls. Apoptosis of AM was evaluated by Apoptag immunohistochemistry. IPF patients received either interferon-g and corticosteroids or azathioprine and corticosteroids for six months. Results . BALF AMs undergoing apoptosis were significantly less in IPF patients. No difference was found in the expression of fas or fas ligand, bcl-2 and bax between IPF and control group. No difference was found between the respiratory function parameters of the two treatment groups after six months. A positive correlation was found between the number of bcl-2 positive stained macrophages and DLCO after treatment. Conclusions . The decreased apoptotic rate of AM of patients with IPF is not associated with decreased expression of apoptosis mediators involved in the external or internal apoptotic pathway.